2018
DOI: 10.1038/s41598-018-31093-2
|View full text |Cite
|
Sign up to set email alerts
|

Population level mitogenomics of long-lived bats reveals dynamic heteroplasmy and challenges the Free Radical Theory of Ageing

Abstract: Bats are the only mammals capable of true, powered flight, which drives an extremely high metabolic rate. The “Free Radical Theory of Ageing” (FTRA) posits that a high metabolic rate causes mitochondrial heteroplasmy and the progressive ageing phenotype. Contrary to this, bats are the longest-lived order of mammals given their small size and high metabolic rate. To investigate if bats exhibit increased mitochondrial heteroplasmy with age, we performed targeted, deep sequencing of mitogenomes and measured point… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 82 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…As more bat reagents become available in the future, it should be possible to elucidate the mechanisms that bats have evolved to coexist with viruses in the absence of disease and this information could be useful for preventing or treating lethal viral infections in humans (55,154).…”
Section: Resultsmentioning
confidence: 99%
“…As more bat reagents become available in the future, it should be possible to elucidate the mechanisms that bats have evolved to coexist with viruses in the absence of disease and this information could be useful for preventing or treating lethal viral infections in humans (55,154).…”
Section: Resultsmentioning
confidence: 99%
“…Logistically it is difficult to study bats in an ageing context, as most are only found in the wild and not easily maintained in captivity 11 . Initial longitudinal ageing studies suggest that the longest-lived genus (Myotis) maintains the length of their telomeres with age without developing cancer 12 and do not show an increased level of mitochondrial damage as expected given their metabolic rate 13 . This is potentially due to adaptations in their DNA repair and maintenance mechanisms 13 .…”
mentioning
confidence: 90%
“…It may well be an essential component in “inflammaging” [ 42 ]. There is some evidence that at least in some species of bat, mitochondrial health, despite bursts of oxidative stress, is maintained by stringent mitochondrial quality control mechanisms, like mitophagy [ 119 ]. Mitophagy is in fact a negative regulator of NLRP3 inflammasome activity, so although mitochondrial damage can activate the inflammasome, it can also activate counter-balancing mitophagy to prevent excessive inflammation [ 120 ].…”
Section: The Immune System Hormesis and Mitochondriamentioning
confidence: 99%